Exploring the relationships between flow, mindfulness, & self-talk : a correlational study - Bervoets, Joachim (2013)
Flow (peak performance) and mindfulness (nonjudgemental present-moment awareness) appear to be conceptually closely related to one another (e.g., Gardner & Moore, 2004). Theoretically, self-talk can be reasoned to play a key role in influencing the afore mentioned constructs. The interconnectivity of these three key variables of interest is illustrated and explained in a proposed overarching theoretical framework. Therefore, the main purpose of the current correlational study was to explore the relationships between flow, mindfulness, and self-talk, at the dispositional level. 212 international participants with experience in competitive sports completed an on-line questionnaire comprising the Dispositional Flow Scale 2 (DFS-2; Jackson & Eklund, 2004), the Five Facet Mindfulness Questionnaire (FFMQ; Baer et al., 2006), and the Automatic Self-Talk Questionnaire for Sports (ASTQS; Zourbanos et al., 2009). Results confirmed the moderate, positive connection between flow and mindfulness (r = .44). Moreover, linear regression analysis indicated that mindfulness appeared to significantly predict flow (F = 50.395 [1, 211], p < .001). Furthermore, negative- and positive self-talk correlated moderately with both flow (r = -.52 and r = .59, respectively) and mindfulness (r = -.45 and r = .23, respectively). Additionally, self-talk (negative and positive combined) significantly predicted flow and mindfulness, accounting for 51% and 22% of the variance, respectively. Investigating potential gender differences in terms of dispositional flow, mindfulness, and self-talk, was a secondary aim of the present study. Significant gender differences were found for every variable of interest; in this sample, men appeared to demonstrate higher levels of flow, mindfulness, and positive self-talk, and lower levels of negative self-talk, in comparison to women. In sum, the examined triangle of concepts appeared to be considerably interconnected, illustrated by moderate to strong correlations and significant predictions. The findings of the present study suggest that these novel avenues of research merit further, closer attention in future studies; especially, making use of experimental designs (intervention-based), more homogenous groups, and deeper analysis of sub-scales. Lastly, future research could benefit greatly from looking into the potential mediating influence mindfulness has on self-talk, and consequently how these two concepts affect athletic peak performance, flow.